Latitudinal environmental gradients and diel variability influence abundance and community structure of Chaetognatha in Red Sea coral reefs. Issue 1 (2nd January 2017) - Al-aidaroos, Ali M.; Karati, Kusum K.; El-sherbiny, Mohsen M.; Devassy, Reny P.; Kürten, Benjamin
Abstract : The Red Sea has been recognized as a unique region to study the effects of ecohydrographic gradients at a basin-wide scale. Its gradient of temperature and salinity relates to the Indian Ocean monsoon and associated wind-driven transport of fertile and plankton-rich water in winter from the Gulf of Aden into the Red Sea. Subsequent evaporation and thermohaline circulation increase the salinity and decrease water temperatures toward the North. Compared with other ocean systems, however, relatively little is known about the zooplankton biodiversity of the Red Sea and how this relates to Red Sea latitudinal gradients. Among the most abundant zooplankton taxa are Chaetognatha, which play an important role as secondary consumers in most marine food webs. Since Chaetognatha are sensitive to changes in temperature and salinity, we surmised latitudinal changes in their biodiversity, community structure and diel variability along the coast of Saudi Arabia. Samples were collected at nine coral reefs spanning approximately 1500 km, from the Gulf of Aqaba in the northern Red Sea to the Farasan Archipelago in the southern Red Sea. Thirteen Chaetognatha species belonging to two families ( Sagittidae and Krohnittidae ) were identified. Latitudinal environmental changes and availability of prey (i.e. Copepoda, Crustacea) altered Chaetognatha density and distribution. The cosmopolitan epiplanktonic Flaccisagitta enflata (38.1%) dominated the Chaetognatha community, and its abundance gradually decreased from South to North. Notable were two mesopelagic species ( Decipisagitta decipiens and Caecosagitta macrocephala ) in the near-reef surface mixed layers at some sites. This was related to wind-induced upwelling of deep water into the coral reefs providing evidence of trophic oceanic subsidies. Most Sagittidae occurred in higher abundances at night, whereas Krohnittidae were more present during the day. Chaetognatha with developing (stage II) or mature ovaries (stage III) were more active at night, demonstrating stage-specific diel vertical migration as a potential predator avoidance strategy.